Symbolic Expression of Bungong Mata Uroe in the Interior Artwork of the Family Room - Jannah, Munadial; Andeska, Niko; Naufa, Miftahun (V-art: Journal of Fine Art, 2023)
Bungong mata uroe is the name for the sunflower plant by people of Aceh, the represented in the form of a sunflower which has beautiful blooming petals and is bright yellow in color with the meaning of loyalty and beauty making the artist interested in visualizing bungong mata uroe into the interior of the family room.The concept used in the creation of works uses the concept of symbolic expression, namely modern art forms that utilize traditional idioms as the basic elements of the creation. The creation method uses four stages, including the pre-design stages, the design stage, the embodiment stage and the presentation stage.In the creation of this final project, the artist expresses the bungong mata uroe which are applied to interior family room products, including corner table mats, wall hangings, mirrors, pillowcases, table mats and window curtains. This work is used to decorate or decorate family rooms as well as to reintroduce the bungong mata uroe shape with a knitting technique that combines two stitching techniques, namely double stitch and chain stitch.